Integrating Islamic Values and Lampung Local Wisdom in Developing Literal Reading Materials for EFL Students - Linda Septiyana; Zuhairi Zuhairi; Muhammad Ali; Kristian Adi Putra (Journal of Innovation in Educational and Cultural Research, 2024)
In the teachings of Islam, reading is considered a command from Allah SWT. Literal reading comprehension means understanding information directly from the written text. This study aims to develop literal reading materials based on Islamic values and Lampung local wisdom. The design is research and development (RD) using Thiagarajan dan Semmel models: define, design, develop, and disseminate (4D). The research participants included a literal reading lecturer and 40 English education study program students. The literal reading materials consist of 9 units and 3 exercises. The study results indicate that Islamic content can provide students with knowledge and understanding of Islamic values and history. Additionally, the materials related to Lampung's local wisdom can enhance students' knowledge and appreciation of local culture. The student's responses to the teaching materials designed were 0% who disagreed, 4,72% less agreed, 42,11% agreed, and 53,17% strongly agreed. The average score is 3.36 and, if converted on a table with a scale of 4, includes in a very good category. Therefore, integrating Islamic values and Lampung local wisdom is worth fostering good manners and preserving local culture.